Miniaturized decoupled slotted patch RFID tag antennas for wearable health care. Issue 1 (12th September 2016) - Aslam, Bilal; Khan, Umar Hasan; Azam, Muhammad Awais; Amin, Yasar; Loo, Jonathan; Tenhunen, Hannu
Abstract: In this article, a couple of two‐layered RFID tag antenna designs exhibiting improved performance descriptors for on‐body applications are presented. The antennas are designed to operate in the microwave band (2.4–2.48 GHz) ensuring high data transmission rates ideal for real‐time subject monitoring applications. The radiating element of both the antennas is a slotted patch structure provisioned with a pair of T‐shaped slots realized on a commercial FR4 substrate. The augmentation of a systematic sequence of narrow comb‐like etchings into the design enhances the impedance bandwidth considerably. A high permittivity silicon layer embedded with the radiating patch provides resilience from the human body dielectric losses. A modified antenna design utilizing patch miniaturization technique, resulting in an overall footprint reduction by 32%, is also proposed. The designed tag antennas offer a gain of more than 1.8 dBi and an attractive read range greater than 6.8 m in the operating band.